STUDI CORPORATE INFORMATION TRANSPARENCY ON THE INTERNET (e-CTI) PADA BURSA EFEK THAILAND, SINGAPURA, MALAYSIA, DAN INDONESIA - Wiwin Wiwin (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this research is to prove the influence of macro factors and micro factors on e-CTI, and compare the value of e-CTI in Thailand, Singapore, Malaysia, and Indonesia. The population of this study are companies listed on the stock exchange of Thailand, Singapore, Malaysia, and Indonesia in 2015. The sample of this study are selected by purposive sampling method and there are 102 companies that fulfill the criteria. Data in this study are analyzed using multiple linear regression. The result indicates that macro factors consisting of legal system, economic development, inflation, and culture, as well as micro factors consisting of independent directors' proportion, and ownership concentration have no effect on e-CTI. However, micro factor such as board of directors’ size is proved to positively affect e-CTI. Country with the highest e-CTI value is Thailand (81.53%), and then followed by Indonesia (78.58%), Singapore (78.48%), and Malaysia (78.09%).